Physics, chemistry and applications of nanostructures : reviews and short notes : proceedings of international conference nanomeeting 2011, Minsk, Belarus, 24-27 May 2011 - Borisenko, V. E. 384246 (Singapore, SI. ; Hackensack, NJ : World Scientific)
Includes bibliographical references and index